2006
DOI: 10.1530/eje.1.02101
|View full text |Cite
|
Sign up to set email alerts
|

Association between an IGF-I gene polymorphism and body fatness: differences between generations

Abstract: Objective: A polymorphism near the promoter region of the IGF-I gene has been associated with serum IGF-I levels, body height and birth weight. In this study, we investigated whether this polymorphism is associated with body composition in young healthy subjects in two cohorts of different generations. Design: Observational study with repeated measurements. Methods: The study group consisted of two comparable young Dutch cohorts with a generational difference of around 20 years. The older cohort consisted of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…This finding does not seem to be influenced either by rhGH replacement or by severity of GHD (no difference in GH peak at stimulation test) or by primary pituitary pathology (no higher prevalence of craniopharyngioma in the noncarrier group). Even though the relatively small number of patients in each group does not allow us to draw consistent conclusions on this topic, the result of a less favorable metabolic profile in noncarriers of the WT allele is in agreement with previous studies in far larger cohorts reporting a higher prevalence of type 2 diabetes and an increased risk of fat accumulation in this genotype (10,28).…”
Section: Discussionsupporting
confidence: 85%
“…This finding does not seem to be influenced either by rhGH replacement or by severity of GHD (no difference in GH peak at stimulation test) or by primary pituitary pathology (no higher prevalence of craniopharyngioma in the noncarrier group). Even though the relatively small number of patients in each group does not allow us to draw consistent conclusions on this topic, the result of a less favorable metabolic profile in noncarriers of the WT allele is in agreement with previous studies in far larger cohorts reporting a higher prevalence of type 2 diabetes and an increased risk of fat accumulation in this genotype (10,28).…”
Section: Discussionsupporting
confidence: 85%
“…23 Another Netherlands (Amsterdam) study found that homozygous carriers of 5¢CA-19, 5¢CA-20 or 5¢CA-19/20 heterozygotes had significantly higher BMI than women with other genotypes, for one of two cohorts examined. 27 We did not investigate these allele groupings specifically, but, inconsistent with these results, grouping 5¢CA-19 and 20 alleles did not yield a significant association with weight or BMI when tested under a recessive model (data not shown). Our study may not, however, have been sufficiently powered to detect the small differences (3 kg) in weight found in the Rotterdam study (n¼2590 women).…”
mentioning
confidence: 84%
“…We have previously found an association of INS VNTR with a gestational duration but not with birth weight [4]. A common promoter region polymorphism of the IGF1 gene, which is associated with circulating IGF-1 levels, has been suggested to affect birth weight, adult height and the risk of type 2 diabetes [1,7,8,9,10,11]. We and others could not replicate an association between variants of the IGF1 promoter region and birth weight [1,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Both polymorphisms have also been suggested to be associated with various measures of body composition, such as body mass index (BMI), fat mass and waist circumference [1,3,5,11,14,15]. To our knowledge, no studies have examined the associations of these common polymorphisms with body composition in infancy and early childhood.…”
Section: Introductionmentioning
confidence: 99%